2022
DOI: 10.1128/spectrum.02445-21
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis Infection Diagnosis among Household Contacts in a High Tuberculosis-Burden Area: a Comparison between Transcript Signature and Interferon Gamma Release Assay

Abstract: The study compares potential of transcript signature and IGRA to diagnose LTBI. It is first of its kind study to screen household contacts (HHCs) in high TB burden area of India. A transcript signature ( FCGR1B, GBP1 , & GBP5 ) is identified as potential biomarker for LTBI. These results can lead to development of point-of-care (POC) like device for LTBI screening in a high TB burdened area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Furthermore, similar low expression levels in TBEx IGRA negative individuals as in LTBI individuals suggests that IGRA test is underdiagnosing LTBI among TB exposed participants. No prior study has speci cally evaluated this phenomenon, although Kaul et al 20 showed no differences in expression for ASUN, NEMF and GBP5, genes that we also evaluated, among IGRA positive vs IGRA negative household contacts in India. The control group used in the Indian cohort were exposed household IGRA negative individuals and their assay diagnostic performance was very low for a combination of markers 20 .…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, similar low expression levels in TBEx IGRA negative individuals as in LTBI individuals suggests that IGRA test is underdiagnosing LTBI among TB exposed participants. No prior study has speci cally evaluated this phenomenon, although Kaul et al 20 showed no differences in expression for ASUN, NEMF and GBP5, genes that we also evaluated, among IGRA positive vs IGRA negative household contacts in India. The control group used in the Indian cohort were exposed household IGRA negative individuals and their assay diagnostic performance was very low for a combination of markers 20 .…”
Section: Discussionmentioning
confidence: 64%
“…GBP5 activates NLRP3 in ammatory vesicle assembly and elicits an in ammatory response to pathogenic bacteria, playing a role in innate immunity and in ammation. Some studies have reported signi cantly increased expression of the GBP5 gene and protein in whole blood of patients with active tuberculosis (19,20). However, no relevant reports on GBP5 in extrapulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…A study found by quantitative real-time polymerase chain reaction (qPCR) technique that FCGR1B gene expression was positively correlated with bacterial load and C-reactive protein in TB patients and also showed good diagnostic power in EPTB (35). One study identi ed a multigene mRNA combination containing the FCGR1B gene as a potential molecular marker for the diagnosis of active tuberculosis (19). FCGR1B may serve as a potential molecular marker for EPTB.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the diagnosis confirmation of LTBI patients still followed the results of the IGRA test (Herrera et al, 2011). Nevertheless, several limitations, such as the large amount of blood needed, limited assay reproducibility, low sensitivity, unknown prognostic value, and slow sample processing, have limited IGRA usage for mass testing (Herrera et al, 2011;Kaul et al, 2022). A recent publication confirmed FCGR1B, GBP1, and GBP5 as the transcript signatures that distinguished between LTB1 and active TB, which could be helpful in screening LTBI on a mass scale (Kaul et al, 2022).…”
Section: Tb Management Benefits From the Utilization Of Immune Biomar...mentioning
confidence: 99%
“…Nevertheless, several limitations, such as the large amount of blood needed, limited assay reproducibility, low sensitivity, unknown prognostic value, and slow sample processing, have limited IGRA usage for mass testing (Herrera et al, 2011;Kaul et al, 2022). A recent publication confirmed FCGR1B, GBP1, and GBP5 as the transcript signatures that distinguished between LTB1 and active TB, which could be helpful in screening LTBI on a mass scale (Kaul et al, 2022). Furthermore, they classified the LTBI into clusters following the IFN-g values in TB1 and TB2 antigens using machine-learning cluster analysis.…”
Section: Tb Management Benefits From the Utilization Of Immune Biomar...mentioning
confidence: 99%